THE ASPECT OF MORPHOLOGICAL STRUCTURES IN ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL ON TENTH GRADE STUDENT’S - Ferdias Prihatna Sari (Wanastra: Jurnal Bahasa dan Sastra, 2019)
Abstract  - This research analyzes about the aspect of morphological structures in textbooks used by senior high school, English Zone and English book. The reason why this topic is chosen since the curiosity demands to know whether the textbooks used in school is fulfilled or not in terms of morphological structure. The Problem discussed is how morphological structures in English Zone and English book are revealed. In order to find out the answer, morphological structure in English textbook for senior high school on tenth grade student is used. From the analyzes, it is found that the aspect of morphological structures are revealed in every word. The student learnt the morphological structures from the easier to the complicated one. Keywords: Morphological structures, morphology, prefix, infix, suffix, inflectional, derivational